Tingkat Keberhasilan Komunikasi Interpersonal dalam Pembelajaran Daring - Diya Illa Darojjah; Iin Purnamasari; Husni Wakhyudin (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The background of this research is that during the COVID-19 pandemic, learning is carried out online which involves no direct meetings between teachers and students, or students toward other students which makes the communication needs is very prioritized in online learning to build successful online learning.  The purpose of this study is to determine the success of the interpersonal communication done by teachers to students in online learning which can be seen from the results of the student scores.  This type of this research uses descriptive qualitative research by collecting data on student questionnaires, student interviews, class teacher interviews, principal interviews, and documentation studies of student scores. The results of the analysis show interpersonal communication in online learning using WhatsApp communication media. Student responses to online learning goes well and the learning objectives are achieved with the results obtained by students in online learning. The results obtained in online learning on average are only 2-6 students who are declared failed passing the minimum completeness criteria of 18 grade 5 students. The results are good with the support of successful communication and good student responses to online learning.  Support from schools and tutoring from parents at home.